Gastric Linitis Plastica and Peritoneal Carcinomatosis as First Manifestations of Occult Breast Carcinoma: A Case Report and Literature Review - Mara Mantiero; Giovanni Faggioni; Alice Menichetti; Matteo Fassan; Valentina Guarneri; Pierfranco Conte (Case Reports in Oncological Medicine)
Gastric linitis plastica is a diffuse involvement of the stomach walls by neoplastic cells. It represents about 3–19% of primitive gastric adenocarcinomas, but it can also be the manifestation of a metastatic disease. Breast cancer is the most frequent malignancy in women, and the metastatic spread to the stomach occurs in less than 10% of the cases. We present an unusual case of gastric linitis plastica and peritoneal carcinomatosis as manifestations of an occult breast cancer in a 53-year-old woman. Imaging and endoscopic evaluation were not able to discriminate a primary from a secondary gastric lesion. The histological evaluation excluded the diagnosis of a primary gastric neoplasia. The IHC profile was consistent with the diagnosis of metastases from the breast cancer. Due to the hormonal receptors’ positivity, we started therapy with fulvestrant (500 mg, day 0, 14, and 28 and every 28 days thereafter by intramuscular injection). After 20 months, the same therapy is still ongoing and well tolerated, while the patient is in good condition with improvement of the dysphagia. Almost 2 years after the diagnosis of linitis plastica, the primitive breast lesion is still occult.